N-terminus GTPase domain of the cytoskeleton protein FtsZ plays a critical role in its adaptation to high hydrostatic pressure - Cui, Xue-Hua; Wei, Yu-Chen; Li, Xue-Gong; Qi, Xiao-Qing; Wu, Long-Fei; Zhang, Wei-Jia (Frontiers in Microbiology, 2024)
Studies in model microorganisms showed that cell division is highly vulnerable to high hydrostatic pressure (HHP). Disassembly of FtsZ filaments induced by HHP results in the failure of cell division and formation of filamentous cells in E. coli. The specific characteritics of FtsZ that allow for functional cell division in the deep-sea environments, especially in obligate piezophiles that grow exclusively under HHP condition, remain enigmatic. In this study, by using a self-developed HHP in-situ fixation apparatus, we compared the pressure tolerance of FtsZ proteins from pressure-sensitive strain Shewanella oneidensis MR-1 (FtsZSo) and obligately piezophilic strain Shewanella benthica DB21MT-2 (FtsZSb). We investigated the effect of HHP on FtsZ by examining the subcellular localization of GFP-tagged FtsZ in vivo and the filament of FtsZ in vitro. Our findings showed that, unlike FtsZSo, HHP hardly affected the Z-ring formation of FtsZSb, and filaments composed of FtsZSb were more stable after incubation under 50 MPa. By constructing chimeric and single amino acid mutated FtsZ proteins, we identified five residues in the N-terminal GTPase domain of FtsZSb whose mutation would impair the Z-ring formation under HHP conditions. Overall, these results demonstrate that FtsZ from the obligately piezophilic strain exhibits superior pressure tolerance than its homologues from shallow water species, both in vivo and in vitro. Differences in pressure tolerance of FtsZ are largely attributed to the N-terminal GTPase domain. This represents the first in-depth study of the adaptation of microbial cytoskeleton protein FtsZ to high hydrostatic pressure, which may provide insights into understanding the complex bioprocess of cell division under extreme environments.